(untitled) (Journal of Asian Development Studies, 2025)
Quality Management Practices (QMP) are essential to an organisation’s performance, but their implementation in the public sector often does not yield consistent results. This finding is particularly relevant for developing economies like Pakistan, where QMP implementation often yields inconsistent results. The study, using data from 540 healthcare employees through a convenience sampling technique in the Federal Capital Territory, Islamabad, and Rawalpindi district, delves deeper by examining the mediating role of the three dimensions of Organisational Commitment (OC). The analysis, conducted using PLS-SEM, reveals that all three dimensions of commitment—affective, continuance, and normative—play a mediating role. The most substantial effect comes from normative commitment. This indicates that QMPs are most effective when they instil a sense of moral obligation and duty in employees, which acts as a powerful motivator within the healthcare setting. According to the findings of the study, there are some theoretical and practical implications for hospital administrators and policymakers. QMP should be implemented as a value-driven strategy to enhance employee commitment. Coming research should involve longitudinal and objective performance metrics to enhance the findings’ generalizability.